A Phase II Trial of Selinexor (KPT‐330) for Metastatic Triple‐Negative Breast Cancer. (17th April 2019) - Shafique, Michael; Ismail‐Khan, Roohi; Extermann, Martine; Sullivan, Dan; Goodridge, Dawn; Boulware, David; Hogue, Deanna; Soliman, Hatem; Khong, Hung; Han, Hyo S.
Abstract: Lessons Learned: Single‐agent selinexor has limited activity in heavily pretreated patients with metastatic triple‐negative breast cancer. Selinexor 60 mg by mouth twice weekly was generally well tolerated with a side‐effect profile consistent with previous clinical trials. Future studies of selinexor in this population should focus on combination approaches and a biomarker‐driven strategy to identify patients most likely to benefit. Background: This phase II trial evaluated the safety, pharmacodynamics, and efficacy of selinexor (KPT‐330), an oral selective inhibitor of nuclear export (SINE) in patients with advanced triple‐negative breast cancer (TNBC). Methods: This phase II trial was designed to enroll 30 patients with metastatic TNBC. Selinexor was given at 60 mg orally twice weekly on days 1 and 3 of each week, three of each 4‐week cycle. The primary objective of this study was to determine the clinical benefit rate (CBR), defined as complete response + partial response + stable disease (SD) ≥12 weeks. Results: Ten patients with a median age of 60 years (range 44–71 years) were enrolled between July 2015 and January 2016. The median number of prior chemotherapy lines was 2 (range 1–5). A planned interim analysis for the first stage per protocol was performed. Three patients had SD and seven had progressive disease. On the basis of these results and predefined stoppage rules, the study was halted. Conclusion: Selinexor was fairly well tolerated in patients with advanced TNBC but did not result in objective responses. However, clinical benefit rate was 30%, and further investigation of selinexor in this patient population should focus on combination therapies.